The Effect of "Fill My Plate" Education Using Leaflets on Balanced Nutrition Knowledge Levels in Eighth Grade Adolescents at SMP Negeri 31 Medan Tuntungan - Monika Helen; Sarah Az-Zahra; Marta Aditya; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2025)
Adolescents are an age group vulnerable to nutritional problems due to limited understanding of a balanced diet. One strategy to improve nutritional literacy in adolescents is through education using simple, attractive, and easy-to-understand media, such as leaflets. This study aims to analyze the effect of leaflet-based "Isi Piringku" education on improving knowledge of balanced nutrition in eighth-grade students at the UPT SMP Negeri 31 Medan Tuntungan. The study design used a quasi-experimental method with a one-group pretest-posttest. The number of respondents was 72 people selected using a simple random sampling technique. The research instrument was a nutritional knowledge questionnaire containing 20 multiple-choice questions. Data were analyzed using a Paired Sample t-Test. The results showed an increase in the average knowledge score from 32.82 before education to 57.64 after the intervention, with a significance value of p = 0.000 (p < 0.05). This proves that education through leaflets has a significant effect on improving students' knowledge of balanced nutrition. Thus, leaflets can be used as an effective, practical, and engaging learning medium to help adolescents understand guidelines for healthy food consumption.